(untitled) (International Current Pharmaceutical Journal, 2014)
The objective of this study was to develop stable lyophilized product of Bivalirudin, a direct thrombin inhibitor with good reconstitution time, % yield of good vials and cake quality. The % loss of crystallinity was determined by DSC for any crystallographic changes of the bulking agent after freeze drying. The glass transition temperature of 5% w/v of Bivalirudin, 3% w/v of mannitol and 0.03% of sodium acetate was approximately ?31°C and the collapse temperature was approximately -28°C. Tubular vials were found to withstand the thermal transition during freeze drying. Water content was inversely proportional to the primary drying set point. Reconstitution time was inversely proportional to annealing temperature and vacuum set point. The % yield of good vials and cake quality was directly proportional to annealing time and primary drying set point. The % loss of crystallinity by DSC was independent of all factors and directly proportional to annealing time. Drying at -10°C results in transition of ? form of mannitol, whereas drying at -7.5°C and -5°C results in ? and ? form of mannitol respectively. On annealing at -7°C for 54 minutes and drying at -6.5°C at 215mT lyophilized product with less than 2% water content, reconstitution time less than 10 seconds, with high yield of more than 95% yield of good vials with best cake quality was obtained. DOI: http://dx.doi.org/10.3329/icpj.v3i5.18533 International Current Pharmaceutical Journal, April 2014, 3(5): 259-264